Respuestas

2013-08-22T23:39:53+02:00
Jocely,
Es un sistema de dos ecuaciones con dos variables. Vamos a determinar la solución:

4x - 11y = - 3      (1)
         4x = 11y - 3                    x = 1/4(11y - 3)
6x + 7y = 19       (2)
         6x = - 7y + 19                 x = 1/6(- 7y + 19)
x = x
                  1/4(11y - 3) = 1/6(- 7y + 19)
                      6(11y - 3) = 4(- 7y + 19)
                      66y - 18 = - 28y + 76
                      66y + 28y = 76 + 18
                                94y = 94
                                                          y = 1
En (1)
                   4x - 11(1) = - 3 
                    4x = - 3 + 11
                    4x = 8                             x = 2